Differences in duration of anticoagulation after pulmonary embolism and deep vein thrombosis: Findings from the SWIss Venous ThromboEmbolism Registry (SWIVTER). Issue 220 (December 2022) - Wenger, Nicolas; Sebastian, Tim; Beer, Jürg H.; Mazzolai, Lucia; Aujesky, Drahomir; Hayoz, Daniel; Engelberger, Rolf P.; Korte, Wolfgang; Voci, Davide; Kucher, Nils; Barco, Stefano; Spirk, David
Abstract: Background: Although the two manifestations of venous thromboembolism (VTE), deep vein thrombosis (DVT) and pulmonary embolism (PE), vary considerably, the consensus guidelines recommend similar algorithms for therapeutic anticoagulation in both conditions. Real-world data assessing contemporary management strategies in PE and DVT alone may help tailoring future recommendations towards more individualized patient care. Methods: In the present analysis, we compared demographics, comorbidities, treatment patterns, and clinical outcomes of PE versus DVT only among 2062 consecutive patients with confirmed VTE enrolled by 11 acute care hospitals between November 2012 and February 2015 in the SWIss Venous ThromboEmbolism Registry (SWIVTER). Results: Overall, 1246 (60 %) patients were diagnosed with PE. In comparison to DVT alone, PE patients were older (66 vs. 59 years; p < 0.001), more frequently had acute and chronic comorbidities, less frequently had prior VTE and hormone replacement, and were less often pregnant. VTE was considered similarly often provoked in patients with PE and DVT alone (33.8 % vs. 33.5 %; p = 0.88). Anticoagulation for an indefinite duration was more often prescribed to patients with PE than those with DVT alone (45.7 vs. 19.6 %; p < 0.001), and PE diagnosis was the strongest independent predictor of indefinite anticoagulation (OR 3.21; 95 % CI 2.55–4.06; p < 0.001). Diagnosis of PE was associated with both increased risk of 90-day mortality (HR 2.31, 95 % CI 1.44–3.71; p = 0.001) and major bleeding (HR 3.88, 95 % CI 1.63–9.22; p = 0.002). Conclusions: Our analysis affirms differences in demographics, risk factors, and clinical outcomes of PE versus DVT alone. In routine clinical practice, duration of anticoagulation is being managed differently between the two manifestations of VTE, in contrast to recommendations of the current consensus guidelines.